Genome-wide screening in human growth plates during puberty in one patient suggests a role for RUNX2 in epiphyseal maturation - Emons, Joyce; Dutilh, Bas E.; Decker, Eva; Pirzer, Heide; Sticht, Carsten; Gretz, Norbert; Rappold, Gudrun; Cameron, Ewan R.; Neil, James C.; Stein, Gary S.; Wijnen, Andre J. van; Wit, Jan Maarten; et al. (The journal of endocrinology, 2011)
In late puberty, estrogen decelerates bone growth by stimulating growth plate maturation. In this study, we analyzed the mechanism of estrogen action using two pubertal growth plate specimens of one girl at Tanner stage B2 and Tanner stage B3. Histological analysis showed that progression of puberty coincided with characteristic morphological changes: a decrease in total growth plate height (P=0.002), height of the individual zones (P<0.001), and an increase in intercolumnar space (P<0.001). Microarray analysis of the specimens identified 394 genes (72% upregulated and 28% downregulated) that changed with the progression of puberty. Overall changes in gene expression were small (average 1.38-fold upregulated and 1.36-fold downregulated genes). The 394 genes mapped to 13 significantly changing pathways (P<0.05) associated with growth plate maturation (e.g. extracellular matrix, cell cycle, and cell death). We next scanned the upstream promoter regions of the 394 genes for the presence of evolutionarily conserved binding sites for transcription factors implicated in growth plate maturation such as estrogen receptor (ER), androgen receptor, ELK1, STAT5B, cyclic AMP response element (CREB), and RUNX2. High-quality motif sites for RUNX2 (87 genes), ELK1 (43 genes), and STAT5B (31 genes), but not ER, were evolutionarily conserved, indicating their functional relevance across primates. Moreover, we show that some of these sites are direct target genes of these transcription factors as shown by ChIP assays.
Gesehen am 29.04.2022